Utilização de histórias em quadrinhos no ensino dos conteúdos de gravitação universal e das leis de Newton - Sousa, Elivelton Ramos de (2021)
Faced with the problem that we have in relation to teaching and learning physics, it is clear that many students have difficulties in this area of teaching. Among the various reasons lead to this difficulty in learning physics content, the lack of resources used in the classroom and the students' lack of interest in physical discipline stand out. Analyzing this problem, we created an educational product to assist the physics teacher during physics classes regarding the contents of Universal Gravitation and Newton's Laws. So that this product will motivate students of the 1st year of high school to learn the contents of the physical discipline. The educational product presents itself as a comic strip magazine. The images used in the magazine were made in an application and the magazine was made in a text editor, where we organize the images as well as the texts worked on.